New Modes of Materiality in the Angoysses douloureuses qui procedent d’amours (1538) by Hélisenne de Crenne - Bromilow, Pollie (Renaissance and Reformation / Renaissance et Réforme, 2024)
This article moves outside the conventional methodologies of visual and literary studies and material bibliography to produce a reading of the Angoysses douloureuses that demonstrates how the text and the material object of the book can be read together to recreate inscribed reading practices, including those of women readers in addition to the reading communities (of women) evoked by the text alone. The narrative of the Angoysses douloureuses displays a preoccupation with representing the materiality of the text throughout the work by means of letters exchanged between the lovers, a single, continuous narrative written by the heroine Helisenne, a manuscript book recuperated from beside her body, and a printed book whose circulation in Paris was sanctioned by Jupiter. This interest in the text’s material form goes beyond representational issues to include woodcuts and chapter headings, showing the capacity of representation to collaborate with the materiality of the printed book in producing meaning. These material elements variously show us how the text seeks to conform to the convention of publishing women’s writing posthumously while also indicating how materiality might both anticipate and shape reading practices. They also allow us to read the material book as one that delineates the problematics of a female-authored work circulating in print at this early point in the sixteenth century.